2023
DOI: 10.3390/jcm12041508
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Lung Volume Appears to Predict Respiratory Morbidity in Congenital Diaphragmatic Hernia

Abstract: Congenital diaphragmatic hernia (CDH) is associated with pulmonary hypoplasia and respiratory morbidity. To assess whether respiratory morbidity during the first 2 years of life in infants with left-sided CDH is associated with fetal lung volume (FLV) evaluated by the observed-to-expected FLV ratio (o/e FLV) on antenatal magnetic resonance imaging (MRI). In this retrospective study, o/e FLV measures were collected. Respiratory morbidity in the first 2 years of life was studied according to two endpoints: treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This is of great interest, seeing as in some places MRI is not readily available, and perhaps VOCAL exploration might be a good alternative if it is easier to access. As we already know, lung volume is the best way of assessing severity and also future respiratory morbidity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is of great interest, seeing as in some places MRI is not readily available, and perhaps VOCAL exploration might be a good alternative if it is easier to access. As we already know, lung volume is the best way of assessing severity and also future respiratory morbidity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have defined prenatal risk factors, such as total fetal lung volume (TFLV), observed-to-expected lung-to-head ratio (o/e LHR) or intrathoracically herniated liver, as predictive factors for the need of extracorporeal membrane oxygenation (ECMO), as well as for survival and (short-term) morbidity [12][13][14][15][16][17][18][19]. Perinatal parameters such as the CDH study group predictive survival score, initial blood gas variables, the Brindle score, the McGoon index, the 12-24 h Score for Neonatal Acute Physiology, Version II (SNAP-II), the need for ECMO, the use of inhaled nitric oxide (iNO) or defect size, which often correlate with each other, have been found to be associated with survival and shortterm morbidity (e.g., duration of ventilation, chylothorax, hemorrhage, length of hospital stay) [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%